Solid-waste-based artificial functional aggregate and preparation method thereof

By using core-shell artificial functional aggregates in the preparation of mud solid waste ceramics, cellulose ether and regulators are used to improve the bonding and density of the ceramics, the problems of high costs, high energy consumption or poor ceramic performance in the existing technology are solved, and the preparation of ceramics with high strength and low water absorption is achieved, supporting its large-scale application.

CN119638236APending Publication Date: 2025-03-18JIANGSU JICUI FUNCTIONAL MATERIALS RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411890695.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing mud solid waste ceramic preparation technology has problems such as high cost, high energy consumption or poor ceramic performance, which limits its large-scale application.

Method used

The preparation method of core-shell artificial functional aggregate is adopted. The core includes mud solid waste, clay minerals, calcium additives, cellulose ethers and regulators. The regulator contains perfluoropolyether alcohol and polysilazane. Through the combination of these components, the water film on the surface of inorganic material particles is destroyed and the adhesion and density are improved.

Benefits of technology

It realizes high strength and low water absorption rate of the ceramite, reduces preparation costs and energy consumption, improves the performance of the ceramite, and supports its large-scale application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638236A_ABST
    Figure CN119638236A_ABST
Patent Text Reader

Abstract

The invention discloses a solid-waste-based artificial functional aggregate and a preparation method thereof, the solid-waste-based artificial functional aggregate comprises an inner core and a shell, and the inner core comprises argillaceous solid waste, clay mineral, a calcium additive, cellulose ether and a regulator; the conditioning agent comprises perfluoropolyether alcohol and polysilazane. The modifier is matched with the cellulose ether, so that damage, regulation and control of the cellulose ether to a water film on the surface of matrix particles can be effectively stabilized, specific hydrophobic groups play a role in reducing the water absorption rate, meanwhile, the modifier can adhere to and fix all components in a system, and the modifier is combined with a hydration product to improve the compactness of the system and play a reinforcing role, so that the ceramsite with high strength and low water absorption rate is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a core-shell type artificial functional aggregate and a preparation method thereof. Background Art

[0002] Muddy solid waste is a solid waste generated in various engineering processes. Due to its complex composition, high water content, poor plasticity, no volcanic ash activity, and high organic content, its comprehensive utilization rate in the field of building materials is low. The existing resource utilization and treatment methods of muddy solid waste are mostly drying and impurity removal, and then ball milling for building materials. The process is complicated and energy-intensive.

[0003] For example, patent CN113603499A discloses a method for firing lightweight ceramsite using shield slag and river sludge. After pre-treating and drying the shield slag and sludge, they are extruded into embryos and sintered. The pre-treatment cost is high, the energy consumption is large, and the carbon emission is high. Patent CN104710156A discloses a non-fired and non-steamed ceramsite made from rail shield slag and its preparation method. The rail shield slag is mixed with cement, quicklime, desulfurized gypsum, fly ash, water glass, and sodium sulfate in a certain proportion, and water is added to form granules. After 28 days of natural curing, the cylinder compressive strength is 3-5MPa and the bulk density is 700kg / m 3 The unburned ceramsite with a water absorption rate of 15%-18% has a long maintenance period and poor performance. The above-mentioned mud solid waste ceramsite preparation technology has high cost, high energy consumption, or poor performance of the prepared ceramsite, which limits its large-scale application. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to provide a solid waste-based artificial functional aggregate, which has good ceramsite performance and can be applied on a large scale. In order to achieve the above purpose, the technical solution adopted by the present invention is: a solid waste-based artificial functional aggregate, including a core and an outer shell, wherein the core includes muddy solid waste, clay minerals, calcium additives, cellulose ether, and a regulator; the regulator includes perfluoropolyether alcohol and polysilazane.

[0005] Cellulose ether has a unique macromolecular chain and functional group structure, and a large number of hydrophilic functional groups on the surface, which can destroy the water film on the surface of inorganic material particles and absorb excess water; it can also change the viscosity of the system and increase the interfacial bonding force, but it will cause the problem of reduced mechanical strength of the system.

[0006] The perfluoropolyether alcohol used in the regulator can cooperate with cellulose ether to destroy the water film on the surface of inorganic material particles, change the surface tension of water and the viscosity of the system, and on the one hand, play a role in bonding the core-shell interface transition zone and improving the interfacial bonding force. At the same time, its hydrophobic groups are arranged in a directional manner to retain water and repel water. It can prevent water molecules from migrating outward during the hydrothermal reaction and causing strength degradation.

[0007] Polysilazane acts as a bridge between cellulose ether and perfluoropolyether alcohol. The Si-OH after hydrolysis can not only couple with the hydroxyl group in cellulose ether, but also play a positive role in the arrangement of the hydration product CSH, making the distribution of the hydration product more uniform. On the one hand, it can effectively avoid the problem of the destruction of the hydrophobic layer of perfluoropolyether alcohol caused by the disordered generation and accumulation of hydration products, thereby improving the product's impermeability. On the other hand, it provides additional attachment points for hydration products to the system, which can improve the adhesion between the inorganic components, improve the system's density, and thus optimize the product's strength.

[0008] Furthermore, the weight ratio of cellulose ether to the regulator is 1:0.1-1.5.

[0009] Illustratively, the weight ratio of cellulose ether to the regulator is 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or a range consisting of any two thereof.

[0010] Furthermore, the weight ratio of cellulose ether to the regulator is 1:0.3-1.

[0011] Further, the weight ratio of perfluoropolyether alcohol to polysilazane in the regulator is 0.01-1.2: 1. Exemplarily, the weight ratio of perfluoropolyether alcohol to polysilazane in the regulator is 0.01: 1, 0.05: 1, 0.1: 1, 0.2: 1, 0.3: 1, 0.4: 1, 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1.0: 1, 1.1: 1, 1.2: 1 or a range consisting of any two thereof.

[0012] Furthermore, the weight ratio of perfluoropolyether alcohol to polysilazane in the regulator is 0.03-0.1:1.

[0013] Furthermore, the regulator accounts for 0.3-2% by weight of the solid waste-based artificial functional aggregate.

[0014] Furthermore, the regulator accounts for 0.5-1.5% by weight of the solid waste-based artificial functional aggregate.

[0015] Further, the regulator includes 0.1-3 parts of perfluoropolyether alcohol and 5-20 parts of polysilazane by weight. For example, the perfluoropolyether alcohol is in the range of 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts or any two thereof; the polysilazane is in the range of 5 parts, 10 parts, 15 parts, 20 parts or any two thereof.

[0016] Furthermore, the preparation method of the regulator is: reacting perfluoropolyether alcohol and polysiloxane in a solvent for 4-8 hours at a reaction temperature of 40-70° C., removing the solvent, and obtaining the regulator.

[0017] Furthermore, in the process of preparing the regulator, the solvent used can dissolve perfluoropolyether alcohol and polysiloxane without specific limitation, such as tetrahydrofuran.

[0018] Furthermore, the inner core includes, by weight, 30-100 parts of muddy solid waste, 5-25 parts of clay minerals, 2-13 parts of calcium additives, 1-5 parts of cellulose ether, and 0.1-5 parts of a regulator.

[0019] Exemplarily, the muddy solid waste is in the range of 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts or any two of them, the clay mineral is in the range of 5 parts, 10 parts, 15 parts, 20 parts, 25 parts or any two of them, the calcium additive is in the range of 2 parts, 5 parts, 7 parts, 10 parts, 13 parts or any two of them, the cellulose ether is in the range of 1 part, 2 parts, 3 parts, 4 parts, 5 parts or any two of them, and the regulator is in the range of 0.1 part, 0.5 part, 1 part, 2 parts, 3 parts, 4 parts, 5 parts or any two of them.

[0020] Furthermore, the inner core includes 35-95 parts of muddy solid waste, 8-21 parts of clay minerals, 4-11 parts of calcium additives, 2-4 parts of cellulose ether, and 0.5-4 parts of a regulator.

[0021] Furthermore, the shell includes 10-45 parts of silicon-alumina powder, 30-100 parts of solid waste powder, and 5-30 parts of calcium additive.

[0022] Exemplarily, the siliceous and aluminous powder is in the range of 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or any two of them; the solid waste powder is in the range of 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts or any two of them; the calcium additive is in the range of 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or any two of them.

[0023] Furthermore, the shell includes 15-40 parts of silicon-alumina powder, 35-92 parts of solid waste powder, and 10-27 parts of calcium additive.

[0024] Furthermore, the muddy solid waste is a mud cake with a moisture content of 10-30%.

[0025] Furthermore, the cellulose ether is selected from at least one of hydroxypropyl methylcellulose and hydroxyethyl methylcellulose.

[0026] Furthermore, the fineness of the solid waste powder is 0.08 mm and the residue on sieve is less than 5%.

[0027] Furthermore, the diameter of the inner core is 4-8 mm; the thickness of the outer shell is 1-4 mm.

[0028] Furthermore, the solid waste powder includes at least one of sandstone tailings, quartz sand tailings, and tailings.

[0029] Furthermore, the muddy solid waste includes at least one of engineering waste, construction waste, sand washing sludge, silt, and sawdust.

[0030] Furthermore, the clay mineral includes at least one of bentonite, kaolin and illite.

[0031] Furthermore, the calcium additive includes at least one of lime, cement and mineral powder.

[0032] Furthermore, the siliceous and aluminous powder includes at least one of fly ash, silica ash and quartz sand.

[0033] A method for preparing the above solid waste-based artificial functional aggregate comprises the following steps: S1. Mix the muddy solid waste with calcium additives and clay minerals, break them up, and send them to a digestion system for digestion to obtain a mixture; S2, mixing the solid waste powder, the silicon-aluminum powder and the calcium additive to obtain a shell mixed powder; S3, mixing the mixture obtained in step S1 with cellulose ether and a regulator to obtain a core mixed powder, and then feeding it into a pelletizing device to form a core; S4, rotating the inner core, spraying the inner core with mist water and adding the outer shell mixed powder to prepare a green body; S5, taking out the green pellets, pre-curing, and obtaining pre-cured ceramsite; S6. The pre-cured expanded clay is sent into a hydrothermal reactor for hydrothermal reaction to obtain artificial functional aggregate.

[0034] Furthermore, in step S3, the kernel mixed powder is formed into a kernel in a spheronizing device at a rotation speed of 10-30 r / min.

[0035] Furthermore, in step S4, the inner core is sprayed with mist water while adding the outer shell mixed powder to form a ball at a speed of 20-40 r / min; the above operation is repeated until a green body meeting the particle size diameter requirements is prepared, and the moisture content accounts for 15-25% of the mass of the system material, and the moisture includes the moisture contained in the muddy solid waste and the mist water supplied by spraying.

[0036] Furthermore, in step S5, the pre-curing temperature is 50-80°C, the humidity is 75-95%, and the time is 0-12h.

[0037] Furthermore, in step S6, the hydrothermal reaction temperature is 100-250° C., the pressure is 1.0-2.0 MPa, and the time is 5-10 h. After the reaction is completed, the temperature is lowered, and the mixture is graded and screened to obtain an artificial functional aggregate.

[0038] The beneficial effects of the present invention are: 1) The core-shell structure solid waste-based artificial functional aggregate prepared in the present application comprises muddy solid waste, clay minerals, calcium additives, cellulose ether and a regulator, wherein the regulator comprises perfluoropolyether alcohol core polysiloxane, and the regulator is combined with cellulose ether to effectively stabilize the destruction and regulation of the water film on the surface of the matrix particles by cellulose ether, and the unique hydrophobic group plays a role in reducing the water absorption rate, and at the same time can adhere to and fix the components in the system, combine with the hydration product to improve the density of the system, play a reinforcing role, and obtain high-strength, low-water-absorption ceramsite.

[0039] 2) The perfluoropolyether alcohol used in the regulator can cooperate with cellulose ether to destroy the water film on the surface of inorganic material particles, change the surface tension of water and the viscosity of the system, and on the one hand, it plays a role in bonding the core-shell interface transition zone and improving the interfacial bonding force. At the same time, its hydrophobic groups are arranged in a directional manner, playing a hydrophobic role, which can prevent water molecules from migrating outward during the hydrothermal reaction and causing strength degradation.

[0040] 3) Polysilazane plays a bridging role on cellulose ether and perfluoropolyether alcohol. The Si-OH after hydrolysis can not only couple with the hydroxyl group in cellulose ether, but also play a positive role in the arrangement of the hydration product CSH, making the distribution of the hydration product more uniform. On the one hand, it can effectively avoid the problem of the destruction of the hydrophobic layer of perfluoropolyether alcohol caused by the disordered generation and accumulation of hydration products, thereby improving the product's impermeability. On the other hand, it provides additional attachment points for hydration products to the system, which can improve the adhesion between the inorganic components, improve the system's density, and thus optimize the product's strength.

[0041] 4) The present invention uses mud solid waste that has not been dried and ground as the raw material for the inner core, and calcium additives as dispersants and stimulants, which can not only effectively disperse the slag, adsorb and degrade organic pollutants in the slag, reduce energy consumption and reduce CO2 emissions, but also stimulate the activity of hydrothermal reactions and improve the overall strength of the inner core and ceramsite.

[0042] 5) The present invention uses sandstone tailings and cement to form an artificial functional aggregate shell. The solid waste powder is rich in silicon and has a composition similar to that of clay minerals. It has good hydrothermal reaction activity and forms a dense and hard ceramsite shell. It not only reduces the raw material cost and shortens the maintenance period, but also avoids the problem of low strength caused by the overall mixing reaction with muddy solid waste, and also prevents the inner core from absorbing external moisture, thereby reducing the overall water absorption rate of ceramsite.

[0043] 6) The present invention adopts a core-shell type ball-forming process, and its structure determines that the artificial functional aggregate has a low elastic modulus, absorbs large impact energy, reduces deformation and cracking, and has good impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0045] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0046] Figure 1 This is a schematic diagram of the solid waste-based artificial functional aggregate of the present invention.

[0047] Among them: 1. Core; 2. Shell. DETAILED DESCRIPTION

[0048] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0049] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0050] The applicant found that the existing preparation technology of clay solid waste-based ceramsite mostly adopts sintering method or non-sintering method, and uses a large amount of water glass, strong alkali, alkali-activated slag material, gypsum, cement and other high-cost materials as binders to prepare solid ceramsite as a whole. At the same time, the degree of pretreatment of clay solid waste is required to be high, which indirectly increases the preparation cost and also brings about the problems of low strength of ceramsite, high bulk density, high water absorption, etc. These problems limit the large-scale application and development of artificial functional aggregates.

[0051] An embodiment of the present invention provides a method for preparing solid waste-based artificial functional aggregate to solve the above problems, which specifically comprises the following steps: S1. Weigh the corresponding weight portions of muddy solid waste, calcium additives, and clay minerals, mix them, stir them fully, break them up evenly, and send them to a digestion system for digestion to obtain a mixture.

[0052] In some embodiments, the digestion time is 0-2 hours.

[0053] In some embodiments, the muddy solid waste is 30-100 parts, the clay mineral is 5-25 parts, and the calcium additive is 2-13 parts.

[0054] In some embodiments, the muddy solid waste is 35-95 parts, the clay mineral is 8-21 parts, and the calcium additive is 4-11 parts.

[0055] In some embodiments, the muddy solid waste is a mud cake with a moisture content of 10-30%.

[0056] In some embodiments, the muddy solid waste includes at least one of engineering waste, construction waste, sand washing sludge, silt, and sawdust.

[0057] In some embodiments, the clay mineral includes at least one of bentonite, kaolin, and illite.

[0058] In some embodiments, the calcium additive includes at least one of lime, cement, and mineral powder.

[0059] S2. Fully and evenly mix the solid waste powder, the silicon-alumina powder and the calcium additive to obtain a shell mixed powder.

[0060] In some embodiments, the silicon-alumina powder is 10-45 parts, the solid waste powder is 30-100 parts, and the calcium additive is 5-30 parts.

[0061] In some embodiments, the amount of silicon-alumina powder is 15-40 parts, the amount of solid waste powder is 35-92 parts, and the amount of calcium additive is 10-27 parts.

[0062] In some embodiments, the fineness of the solid waste powder is 0.08 mm and the residue on sieve is less than 5%.

[0063] In some embodiments, the siliceous and aluminous powder includes at least one of fly ash, silica ash, and quartz sand.

[0064] In some embodiments, the solid waste powder includes at least one of sandstone tailings, quartz sand tailings, and tailings.

[0065] In some embodiments, the calcium additive includes at least one of lime, cement, and mineral powder.

[0066] S3, mixing the mixture obtained in step S1 with cellulose ether and a regulator, and stirring them thoroughly to obtain a core mixed powder, which is then fed into a pelletizing device to form a core at a speed of 10-30 r / min. The core has a diameter of 4-8 mm.

[0067] In some embodiments, the cellulose ether is 1-5 parts, and the regulator is 0.1-5 parts.

[0068] In some embodiments, the cellulose ether is 2-4 parts and the regulator is 0.5-4 parts.

[0069] In some embodiments, the weight ratio of cellulose ether to conditioning agent is 1:0.1-1.5.

[0070] In some embodiments, the weight ratio of cellulose ether to conditioning agent is 1:0.3-1.

[0071] In some embodiments, the cellulose ether is selected from at least one of hydroxypropyl methylcellulose and hydroxyethyl methylcellulose.

[0072] In some embodiments, the regulator includes 0.1-3 parts of perfluoropolyether alcohol and 5-20 parts of polysilazane, wherein the parts of perfluoropolyether alcohol and polysilazane are only used to indicate the weight ratio of the added amounts of the two and have no corresponding relationship with the parts of the regulator.

[0073] In some embodiments, the weight ratio of perfluoropolyether alcohol to polysilazane is 0.01-1.2:1.

[0074] In some embodiments, the weight ratio of perfluoropolyether alcohol to polysilazane is 0.03-0.1:1.

[0075] In some embodiments, the preparation method of the regulator is: reacting perfluoropolyether alcohol and polysiloxane in tetrahydrofuran solvent for 4-8 hours at a reaction temperature of 40-70° C., and removing the solvent to obtain the regulator.

[0076] S4, spraying the inner core with mist water while adding the outer shell mixed powder, and forming into balls at a speed of 20-40 r / min; during the process, the above operation is continuously repeated until a green body with an outer shell thickness of 1-4 mm is prepared.

[0077] Water accounts for 15-25% of the system material mass, including the water contained in the muddy solid waste and the mist water supplied by spraying.

[0078] S5. Take out the green clay, place it in a curing environment at 50-80° C. and 75-95% humidity for pre-curing for 0-12 hours to obtain pre-cured ceramsite.

[0079] S6. The pre-cured ceramsite is fed into a hydrothermal reactor and reacted at 100-250°C and 1.0-2.0MPa for 5-10 hours. After the reaction is completed, the temperature is lowered, and the mixture is graded and sieved to obtain an artificial functional aggregate.

[0080] In some embodiments, the regulator accounts for 0.3-2% by weight of the solid waste-based artificial functional aggregate.

[0081] In some embodiments, the modifier accounts for 0.5-1.5% by weight of the solid waste-based artificial functional aggregate.

[0082] like Figure 1 As shown, the prepared ceramsite includes a core 1 and a shell 2.

[0083] Example The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0084] Example 1 A method for preparing solid waste-based artificial functional aggregate comprises the following steps: S1. Weigh 56.8 parts of construction waste soil, 6.2 parts of quicklime and 12.5 parts of bentonite, mix them, stir them thoroughly, break them up evenly, and send them into the digestion system for digestion for 1 hour to obtain a mixture.

[0085] The construction waste soil is a mud cake with a moisture content of 20%.

[0086] S2. Fully and evenly mix 55 parts of sandstone tailings, 23.5 parts of fly ash and 16.2 parts of Portland cement to obtain a shell mixed powder.

[0087] The fineness of sandstone tailings is 0.08mm and the residue on sieve is less than 5%.

[0088] S3, the mixture obtained in step S1 is mixed with 2.8 parts of cellulose ether and 1.7 parts of a regulator, and stirred thoroughly to obtain a core mixed powder, which is then fed into a pelletizing device to form a core at a speed of 15 r / min. The core has a diameter of 6 mm.

[0089] After calculation, the weight ratio of cellulose ether to regulator is 2.8:1.7=1:0.6.

[0090] The regulator includes 0.7 parts of perfluoropolyether alcohol and 12 parts of polysilazane, and the weight ratio of perfluoropolyether alcohol to polysilazane is 0.7:12=0.06:1.

[0091] The preparation method of the regulator is as follows: reacting perfluoropolyether alcohol and polysiloxane in a weight ratio of 0.06:1 in a solvent of tetrahydrofuran for 6 hours at a reaction temperature of 55° C., and removing the solvent to obtain the regulator.

[0092] S4, spraying the inner core with mist water while adding the outer shell mixed powder, forming balls at a speed of 30r / min; repeating the above operation until a green body that meets the particle size requirements is prepared, the green body diameter is 8mm, the inner core diameter is 6mm; the outer shell thickness is 2mm. The total amount of the sprayed mist water and the water content in the engineering slag soil accounts for 25% of the total mass of the ceramsite.

[0093] S5. Take out the green clay, place it in a curing environment at 65° C. and 85% humidity for pre-curing for 6 hours to obtain pre-cured ceramsite.

[0094] S6. The pre-cured expanded clay is fed into a vertical hydrothermal reactor and reacted at 190°C and 1.2 MPa for 8 hours. After the reaction is completed, the temperature is lowered, and the mixture is graded and sieved to obtain artificial functional aggregate.

[0095] It is calculated that the regulator accounts for 1.7 / (56.8+12.5+6.2+2.8+1.7+23.5+55+16.2)*100%=0.97% of the weight of solid waste-based artificial functional aggregate.

[0096] Example 2 A method for preparing solid waste-based artificial functional aggregate comprises the following steps: S1. Weigh 36.2 parts of construction waste soil, 4 parts of quicklime and 8 parts of bentonite, mix them, stir them thoroughly, break them up evenly, and send them into the digestion system for digestion for 0.5 hours to obtain a mixture.

[0097] The construction waste soil is a mud cake with a moisture content of 20%.

[0098] S2. Fully and evenly mix 35 parts of sandstone tailings, 15 parts of fly ash and 10.3 parts of Portland cement to obtain a mixed powder for the outer shell.

[0099] The fineness of sandstone tailings is 0.08mm and the residue on sieve is less than 5%.

[0100] S3, the mixture obtained in step S1 is mixed with 2.3 parts of cellulose ether and 0.7 parts of a regulator, and stirred thoroughly to obtain a core mixed powder, which is then fed into a pelletizing device to form a core at a speed of 15 r / min. The core has a diameter of 6 mm.

[0101] After calculation, the weight ratio of cellulose ether to the regulator is 2.3:0.7=1:0.3.

[0102] The regulator includes 0.5 parts of perfluoropolyether alcohol and 15 parts of polysilazane, and the weight ratio of perfluoropolyether alcohol to polysilazane is 0.5:15=0.03:1.

[0103] The preparation method of the regulator is as follows: reacting perfluoropolyether alcohol and polysiloxane in a weight ratio of 0.03:1 in a solvent of tetrahydrofuran for 8 hours at a reaction temperature of 40° C., and removing the solvent to obtain the regulator.

[0104] S4, spraying the inner core with mist water while adding the outer shell mixed powder, forming balls at a speed of 30r / min; repeating the above operation until a green body that meets the particle size requirements is prepared, the green body diameter is 8mm, the inner core diameter is 6mm; the outer shell thickness is 2mm. The total amount of the sprayed mist water and the water content in the engineering slag soil accounts for 25% of the total mass of the ceramsite.

[0105] S5. Take out the green clay, place it in a curing environment at 80° C. and 75% humidity for pre-curing for 4 hours to obtain pre-cured ceramsite.

[0106] S6. The pre-cured expanded clay is fed into a vertical hydrothermal reactor and reacted at 180°C and 1 MPa for 10 hours. After the reaction is completed, the temperature is lowered, and the mixture is graded and sieved to obtain artificial functional aggregate.

[0107] It is calculated that the regulator accounts for 0.7 / (36.2+8+4+2.3+0.7+15+35+10.3)*100%=0.63% of the weight of solid waste-based artificial functional aggregate.

[0108] Example 3 A method for preparing solid waste-based artificial functional aggregate comprises the following steps: S1. Weigh 95 parts of construction waste soil, 10.5 parts of quicklime and 21 parts of bentonite, mix them, stir them thoroughly, break them up evenly, and send them into the digestion system for digestion for 2 hours to obtain a mixture.

[0109] The construction waste soil is a mud cake with a moisture content of 20%.

[0110] S2. Fully and evenly mix 92 parts of sandstone tailings, 39.5 parts of fly ash and 27 parts of Portland cement to obtain a shell mixed powder.

[0111] The fineness of sandstone tailings is 0.08mm and the residue on sieve is less than 5%.

[0112] S3. The digested material is mixed with 3.8 parts of cellulose ether and 3.7 parts of a regulator, and stirred thoroughly to obtain a core mixed powder, which is then sent to a pelletizing device to form a core at a speed of 15 r / min. The core has a diameter of 6 mm.

[0113] After calculation, the weight ratio of cellulose ether to regulator is 3.8:3.7=1:0.97.

[0114] The regulator includes 1 part of perfluoropolyether alcohol and 10 parts of polysilazane, and the weight ratio of perfluoropolyether alcohol to polysilazane is 1:10=0.1:1.

[0115] The preparation method of the regulator is as follows: reacting perfluoropolyether alcohol and polysiloxane in a weight ratio of 0.1:1 in a solvent of tetrahydrofuran for 4 hours at a reaction temperature of 70° C., and removing the solvent to obtain the regulator.

[0116] S4. Spray the inner core with mist water while adding the outer shell mixed powder to form a ball at a speed of 30r / min. Repeat the above operation until a green body that meets the particle size diameter requirements is prepared. The green body diameter is 8mm, of which the inner core diameter is 6mm; the outer shell thickness is 2mm.

[0117] S5. Take out the green clay, place it in a curing environment of 50° C. and 95% humidity for pre-curing for 8 hours to obtain pre-cured ceramsite.

[0118] S6. The pre-cured expanded clay is fed into a vertical hydrothermal reactor and reacted at 200°C and 1.4 MPa for 6 hours. After the reaction is completed, the temperature is lowered, and the mixture is graded and sieved to obtain artificial functional aggregate.

[0119] It is calculated that the regulator accounts for 3.7 / (95+21+10.5+3.8+3.7+39.5+92+27)*100%=1.26% of the weight of solid waste-based artificial functional aggregate.

[0120] Example 4 The preparation methods of this embodiment and embodiment 1 are basically the same, the main difference is that the regulator in this embodiment includes 0.2 parts of perfluoropolyether alcohol and 12.5 parts of polysiloxane. After calculation, the weight ratio of perfluoropolyether alcohol to polysiloxane is 0.2:12.5=0.016:1.

[0121] Example 5 The preparation methods of this embodiment are basically the same as those of embodiment 1, the main difference being that the regulator in this embodiment includes 6.7 parts of perfluoropolyether alcohol and 6 parts of polysiloxane. After calculation, the weight ratio of perfluoropolyether alcohol to polysiloxane is 6.7:6=1.12:1.

[0122] Example 6 The preparation methods of this embodiment and embodiment 1 are basically the same, the main difference is that in the kernel mixed powder of this embodiment, the number of cellulose ether added is 3.8 parts, and the number of regulators added is 0.7 parts. After calculation, the weight ratio of cellulose ether to regulator is 3.8:0.7=1:0.18.

[0123] Example 7 The preparation methods of this embodiment and embodiment 1 are basically the same, the main difference is that in the kernel mixed powder of this embodiment, the number of cellulose ether added is 2 parts, and the number of regulators added is 2.5 parts. After calculation, the weight ratio of cellulose ether to regulator is 2:2.5=1:1.25.

[0124] Comparative Example 1 The preparation methods of this comparative example and Example 1 are basically the same, the main difference being that no polysilazane is added to the regulator in this example, that is, the regulator is perfluoropolyether alcohol.

[0125] Comparative Example 2 The preparation methods of this comparative example and Example 1 are basically the same, the main difference being that no perfluoropolyether alcohol is added to the regulator in this example, that is, the regulator is polysilazane.

[0126] Test Case The performance of the ceramsite prepared in Examples 1-7 and Comparative Examples 1-2 was tested, and the cylinder pressure strength, water absorption rate, and bulk density were measured in accordance with GB / T17431-2010 "Light Aggregates and Test Methods Thereof". The test results are shown in Table 1 below: Table 1 Performance data of ceramsite

[0127] It can be seen from Examples 1-3 that the ceramsite prepared by the present invention has good performance, with a cylinder pressure strength of ≥13.7Mpa, a water absorption rate of ≤7.9%, and a bulk density of ≤802kg / m 3 .

[0128] Compared with Example 1, Example 4 shows that the amount of perfluoropolyether alcohol used in Example 4 is too small, and the improvement effect of the regulator on the hydrophobicity and dispersibility of the inorganic material particles in the system is weakened, so the water absorption rate of the expanded clay is deteriorated; at the same time, it can be seen that a larger amount of polysilazane, although theoretically more conducive to the uniform distribution of hydration products to optimize the strength of expanded clay, but from the data point of view, it does not have a more obvious optimization effect on the strength of expanded clay.

[0129] Compared with Example 1, in Example 5, the proportion of perfluoropolyether alcohol in the regulator is too high, and the hydrophobic film of the inorganic material particles in the system is thicker. Although it can give the expanded clay better impermeability, it will increase the resistance of water molecules to migrate into the interior of the green body during the hydrothermal reaction, affecting the degree of hydrothermal reaction. At the same time, too little polysilazane may lead to uneven distribution of hydration products in the system, thereby damaging the hydrophobic layer of perfluoropolyether alcohol and reducing the overall strength of the product. Therefore, the cylinder compressive strength and bulk density of the expanded clay are deteriorated.

[0130] Compared with Example 1, in Example 6, the amount of regulator used in the system is too small, which may lead to the deterioration of the hydrophobicity and dispersibility of the surface of the inorganic material particles. At the same time, it also leads to the deterioration of the distribution uniformity of the hydration product, thereby affecting the adhesion, density and impermeability of the system. Therefore, the cylinder pressure strength, water absorption rate and bulk density of the expanded clay are all deteriorated.

[0131] Compared with Example 1, in Example 7, the amount of the regulator is relatively increased, which can effectively improve the anti-seepage performance, and can provide more hydrothermal product attachment points for the system, which has a positive effect on the strength of the system. However, if the amount of cellulose ether is too small, it may lead to a decrease in the degree of water film destruction on the surface of the inorganic material particles, affecting its dispersibility and further affecting the strength. From the data, the various properties of ceramsite do not change much.

[0132] Compared with Example 1, in Comparative Example 1, perfluoropolyether alcohol and cellulose ether are directly bonded to form a hydrophobic film. Due to the absence of polysilazane, on the one hand, the disordered generation and accumulation of hydration products in the system may cause the destruction of the hydrophobic film and affect the impermeability of the ceramsite; on the other hand, the attachment points of the hydration products in the system are reduced, which reduces the adhesion between the inorganic materials and affects the strength. Therefore, the cylinder pressure strength of the ceramsite decreases and the packing density increases.

[0133] Compared with Example 1, in Comparative Example 2, the absence of perfluoropolyether alcohol reduces the impermeability of the system. At the same time, the dispersion uniformity of the inorganic material particles decreases, and during the hydration process, water molecules may migrate outward, resulting in fine cracks inside the expanded clay and a significant decrease in strength. From the data, the packing density of the expanded clay also increases.

[0134] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0135] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0136] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

[0137] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A solid waste-based artificial functional aggregate, characterized in that: It comprises a core and a shell, wherein the core comprises muddy solid waste, clay minerals, calcium additives, cellulose ether, and a regulator; The regulator includes perfluoropolyether alcohol and polysilazane.

2. The solid waste-based artificial functional aggregate according to claim 1, characterized in that: The weight ratio of the cellulose ether to the regulator is 1:0.1-1.5; The weight ratio of perfluoropolyether alcohol to polysilazane in the regulator is 0.01-1.2:1; The regulator accounts for 0.3-2% of the weight of the solid waste-based artificial functional aggregate.

3. The solid waste-based artificial functional aggregate according to claim 1, characterized in that: The weight ratio of the cellulose ether to the regulator is 1:0.3-1; The weight ratio of perfluoropolyether alcohol to polysilazane in the regulator is 0.03-0.1:

1.

4. The solid waste-based artificial functional aggregate according to claim 1, characterized in that: The regulator includes 0.1-3 parts of perfluoropolyether alcohol and 5-20 parts of polysilazane by weight; The regulator accounts for 0.5-1.5% of the weight of the solid waste-based artificial functional aggregate.

5. The solid waste-based artificial functional aggregate according to claim 1, characterized in that: The preparation method of the regulator is as follows: reacting perfluoropolyether alcohol and polysiloxane in a solvent for 4-8 hours, removing the solvent, and obtaining the regulator.

6. The solid waste-based artificial functional aggregate according to claim 1, characterized in that: By weight, The inner core comprises 30-100 parts of muddy solid waste, 5-25 parts of clay minerals, 2-13 parts of calcium additives, 1-5 parts of cellulose ether, and 0.1-5 parts of a regulator; The shell comprises 10-45 parts of silicon-alumina powder, 30-100 parts of solid waste powder, and 5-30 parts of calcium additive; The muddy solid waste is a mud cake with a moisture content of 10-30%; The cellulose ether is selected from at least one of hydroxypropyl methylcellulose and hydroxyethyl methylcellulose; the fineness of the solid waste powder is 0.08 mm and the residue on the sieve is less than 5%; The solid waste powder includes at least one of sandstone tailings, quartz sand tailings, and tailings.

7. The solid waste-based artificial functional aggregate according to claim 1, characterized in that: By weight, the inner core comprises 35-95 parts of muddy solid waste, 8-21 parts of clay minerals, 4-11 parts of calcium additives, 2-4 parts of cellulose ether, and 0.5-4 parts of a regulator; The shell comprises 15-40 parts of silicon-alumina powder, 35-92 parts of solid waste powder and 10-27 parts of calcium additive.

8. The solid waste-based artificial functional aggregate according to claim 7, characterized in that: The diameter of the inner core is 4-8 mm; the thickness of the outer shell is 1-4 mm; The muddy solid waste includes at least one of engineering slag, building slag, sand washing bottom mud, silt and sawdust; The clay mineral includes at least one of bentonite, kaolin and illite; The calcium additive includes at least one of lime, cement and mineral powder; The silicon-alumina powder includes at least one of fly ash, silica ash and quartz sand.

9. The method for preparing solid waste-based artificial functional aggregate according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mix the muddy solid waste, calcium additives and clay minerals, break them up, and send them into a digestion system to obtain a mixture; S2, mixing the solid waste powder, the silicon-aluminum powder and the calcium additive to obtain a shell mixed powder; S3, mixing the mixture obtained in step S1 with cellulose ether and a regulator to obtain a core mixed powder, and then feeding it into a pelletizing device to form a core; S4, rotating the inner core, spraying water on the inner core and adding the outer shell mixed powder to prepare a green body; S5, taking out the green pellets, pre-curing, and obtaining pre-cured ceramsite; S6. The pre-cured expanded clay is sent into a hydrothermal reactor for hydrothermal reaction to obtain artificial functional aggregate.

10. The method for preparing solid waste-based artificial functional aggregate according to claim 9, characterized in that: In step S5, the pre-curing temperature is 50-80°C, the humidity is 75-95%, and the time is 0-12h; In step S6, the hydrothermal reaction temperature is 100-250° C., the pressure is 1.0-2.0 MPa, and the reaction time is 5-10 h.

Citation Information

Patent Citations

  • Rail shield muck unburned and non-autoclaved ceramsite and preparation method thereof

    CN104710156A